Síndrome de Burnout en el Personal Policial Técnico Operativo del Distrito 01 Loja, periodo 2021 - Benitez Cabrera, Nicole Anabel (2022)
The Burnout Syndrome affects the person as well as the organization. Causing emotional problems, negative attitude, aggressive behavior, dependence on alcohol or other substances, family problems; and somatic indices such as cardiovascular alterations, immunological, sexual, muscular, digestive problems; regarding to the organization, it can affect the deterioration of the quality of care, work absenteeism, a tendency to abandon the organization, and an increase in interpersonal conflicts, among other problems. The objective of the following research was to determine the Burnout Syndrome and certain sociodemographic factors that can affect its development, with a sample of 131 participants that make up the Technical Police Operational Staff of District 01 Loja, the methodology used was descriptive, quantitative and cutting crosssectional, the Maslach Burnout Inventory and Human Services Survey (MBI-HSS) was used. The results show low emotional exhaustion, low depersonalization and high personal fulfillment. Obtaining in this way, a lower level of Burnout Syndrome in the participants of the present investigation. In addition, that sociodemographic factors such as: sex, age, marital status and employment status are not predisposing factors for the development of the syndrome